2015
DOI: 10.15537/smj.2015.8.11533
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal short-term outcomes in infants with intrauterine growth restriction

Abstract: Objectives:To assess the neonatal outcomes in newborns with intrauterine growth restriction (IUGR) in a Romanian population in a 3 level maternity unit.Methods:A matched case-control design, with one control for each patient was used. The case group comprised neonates with birth weight and birth length below the 10th percentile for the gestational age. Individual matching by gender and age of gestation was used to identify the control group. Both cases and controls were selected from the infants admitted to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Metabolic morbidities, such as neonatal hypoglycemia, hypocalcemia, or hyperbilirubinemia requiring phototherapy, are more common in late preterm births compared to full term births [3]. Our results show that the rate of hypoglycemia was higher in the iLPTB group than in the sLPTB group, without differences in the GDM rate [17] [18].…”
Section: Discussionmentioning
confidence: 56%
“…Metabolic morbidities, such as neonatal hypoglycemia, hypocalcemia, or hyperbilirubinemia requiring phototherapy, are more common in late preterm births compared to full term births [3]. Our results show that the rate of hypoglycemia was higher in the iLPTB group than in the sLPTB group, without differences in the GDM rate [17] [18].…”
Section: Discussionmentioning
confidence: 56%
“…Hasmasanu et al conducted a study in 2013 which revealed that 27.3% of the IUGR neonates developed hypoglycemia while 4.3% of the AGA babies did so. 13 Similarly, Mazumder et al studied the correlation of hypoglycemia in IUGR neonates and observed a much higher incidence (46.9%) compared to 3.1% among term AGA neonates. 8 Lubchenco et al found that 25% of term IUGR neonates presented with hypoglycemia compared to 10% among term AGA neonates.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies 23 reported no association of neonatal brain injury with IUGR, whereas others found significantly higher percentage of infants with intraventricular hemorrhage in the IUGR group compared with controls. 24 Also, the effect of chorioamnionitis on ICH is not straightforward. 25 While some findings indicated no association 26 between chorioamnionitis and intraventricular hemorrhage, others recognized chorioamnionitis as a risk factor of intraventricular hemorrhage.…”
Section: Discussionmentioning
confidence: 99%